Electrode active material, method for producing same, electrode mixture, and battery
By optimizing the structure of hard carbon in the battery, ensuring that it has specific characteristics in the Raman spectrum, forming electrode active substances with nanographite structures, solving the problem of insufficient capacity at low potentials in the prior art, and achieving improvement in battery performance.
Patent Information
- Application Number
- CN202411556235.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-26
- Filing Date
- 2024-11-04
- Publication Date
- 2025-06-27
AI Technical Summary
In the prior art, there is room for improvement in the capacity of cells containing hard carbon as electrode active substances at low potentials.
By optimizing the structure of hard carbon under specific conditions in the Raman spectrum, the hard carbon has a G' band, a G band and a D band, and the intensity ratio of the G' band to the G band and the half-maximum width of the D band is controlled to form an electrode active material with a nanographite structure.
The capacity performance of the battery at low potential is significantly improved and the overall performance of the battery is improved.
Smart Images

Figure CN120221647A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrode active material, a method for manufacturing the same, an electrode mixture, and a battery. Background Art
[0002] As disclosed in Patent Documents 1 and 2, a battery containing hard carbon as a negative electrode active material has been developed.
[0003] Prior Art Documents
[0004] Patent Document 1: International Publication No. 2012 / 147242
[0005] Patent Document 2: Japanese Patent Application Laid-Open No. 2021-012872 Summary of the Invention
[0006] In a battery containing hard carbon as an electrode active material, there is room for improvement in the capacity at a low potential.
[0007] An object of the present disclosure is to provide an electrode active material containing hard carbon, which can improve the capacity at a low potential, a method for manufacturing the same, an electrode mixture containing such an electrode active material, and a battery containing such an electrode mixture.
[0008] The present applicant has found that the above problems can be solved by the following means.
[0009] <Solution 1>
[0010] An electrode active material is an electrode active material containing hard carbon,
[0011] The hard carbon has a G' band, a G band, and a D band in a Raman spectrum,
[0012] The intensity I of the G' band G’ Relative to the intensity I of the G band G The ratio I G’ / I G Is 0.05 or more, and
[0013] The full width at half maximum Hw of the D band D Is 50 or more and 160 or less.
[0014] <Solution 2>
[0015] The electrode active material according to Solution 1, wherein the full width at half maximum Hw of the D band D Is 90 or more and 130 or less.
[0016] <Solution 3>
[0017] The electrode active material according to Solution 1 or 2, wherein the intensity I of the D band DThe ratio I of the intensity I of the D band relative to the intensity I of the G band G is D / I G is 1.0 or more and 1.6 or less.
[0018] <Solution 4>
[0019] For the electrode active material according to Solution 3, the ratio I of the intensity I of the D band relative to the intensity I of the G band D is G is D / I G is 1.2 or more and 1.4 or less.
[0020] <Solution 5>
[0021] An electrode mixture containing the electrode active material according to any one of Solutions 1 to 4.
[0022] <Solution 6>
[0023] A battery
[0024] successively has a negative electrode current collector layer, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer, and
[0025] either the negative electrode active material layer or the positive electrode active material layer contains the electrode mixture according to Solution 5.
[0026] <Solution 7>
[0027] For the battery according to Solution 6, the negative electrode active material layer contains the electrode mixture according to Solution 5.
[0028] <Solution 8>
[0029] For the battery according to Solution 6 or 7, it is a sodium ion battery in which the electrolyte layer has sodium ions.
[0030] <Solution 9>
[0031] For the battery according to Solution 8, it is a liquid system battery in which the electrolyte layer contains an electrolytic solution having sodium ions.
[0032] <Solution 10>
[0033] For the battery according to Solution 8, it is a solid battery in which the electrolyte layer contains a solid electrolyte having sodium ions.
[0034] <Solution 11>
[0035] A method for manufacturing the electrode active material according to any one of Solutions 1 to 4, including the following steps:
[0036] Provide a carbon-containing raw material; and
[0037] The raw material is fired in an inert atmosphere containing more than 0% and less than 1.0% of the atmosphere to carbonize it.
[0038] According to the present disclosure, it is possible to provide a hard carbon-containing electrode active material capable of improving the capacity at a low potential, a method for manufacturing the same, an electrode mixture containing such an electrode active material, and a battery containing such an electrode mixture. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is a schematic cross-sectional view showing an example of the battery of the present disclosure.
[0040] Figure 2 is the Raman spectrum of the electrode active material of Example 1.
[0041] Figure 3 is the Raman spectrum of the electrode active material of Comparative Example 3.
[0042] Figure 4 is a coordinate diagram showing the capacities of the batteries of the respective examples and comparative examples at a low potential (below 0.05 V (vs. Na / Na + ))
[0043] DESCRIPTION OF REFERENCE NUMERALS
[0044] 100 Battery
[0045] 110 Negative electrode current collector layer
[0046] 120 Negative electrode active material layer
[0047] 130 Electrolyte layer
[0048] 140 Positive electrode active material layer
[0049] 150 Positive electrode current collector layer DETAILED DESCRIPTION
[0050] Hereinafter, embodiments of the present disclosure will be described in detail. Furthermore, the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the disclosed gist.
[0051] <<Electrode Active Material>>
[0052] The electrode active material of the present disclosure contains hard carbon, and the hard carbon has a G' band, a G band, and a D band in the Raman spectrum. The intensity I of the G' band G’ relative to the intensity I of the G band G of the ratio I G’ / I G is 0.05 or more. The full width at half maximum Hw of the D band Dis 50 or more and 160 or less.
[0053] In the past, in order to determine the structure of hard carbon, measurements based on Raman spectroscopy were carried out. In this regard, the applicant of the present application surprisingly found that an electrode active material of hard carbon, which includes a G' band (referred to as "2D band" in Patent Document 2) having a predetermined size in the Raman spectrum and having a moderate full width at half maximum of the D band, can improve the capacity of the battery at a low potential.
[0054] Hard carbon does not have a structure in which graphene is stacked in an orderly manner like graphite, but has a structure in which graphene is aggregated disorderly. On the other hand, the G' band is caused by the stacked structure of graphene. That is, the fact that the electrode active material of the present disclosure has a G' band indicates that the electrode active material of the present disclosure has a minute stacked structure of graphene (nano-graphite structure).
[0055] The full width at half maximum of the D band is caused by the defects of the microcrystalline structure. For example, a small full width at half maximum of the D band of the electrode active material indicates few defects in the microcrystalline structure.
[0056] That is, it is presumed that an electrode active material having a nano-graphite structure and having a moderate number of defects in the microcrystalline structure can improve the capacity of the battery at a low potential.
[0057] Furthermore, regarding the present disclosure, the "electrode active material" can be used as both the "positive electrode active material" and the "negative electrode active material", and particularly as the "negative electrode active material".
[0058] The electrode active material of the present disclosure includes hard carbon. The content of hard carbon can be 50% by mass or more, 70% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more, relative to the total amount of the electrode active material, and can also be 100% by mass. That is, the electrode active material can be hard carbon. The average particle diameter of the hard carbon is not particularly limited, and can be set in the range of 50 nm to 100 μm, for example.
[0059] Hard carbon has a G' band, a G band, and a D band in the Raman spectrum.
[0060] Regarding the present disclosure, in the Raman spectrum of the electrode active material, the peaks confirmed around 2800 - 2600 cm -1 、1600 cm -1 and 1350 cm -1 can be respectively judged as the G' band, the G band, and the D band.
[0061] The intensity I G’ of the G' band relative to the intensity I G of the G band, the ratio I G’ / I G is 0.05 or more. This ratio I G’ / IG It can be 0.05 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and can be 1.0 or less, 0.8 or less, 0.5 or less, or 0.4 or less. In particular, this ratio I G’ / I G can be 0.3 or more and 0.4 or less.
[0062] Furthermore, the G' band is caused by the number of graphene layers, i.e., the stacked structure, and the G band is caused by the planar structure from the sp 2 orbital. Therefore, I G’ / I G represents the ratio of the stacked structure of the electrode active material to the planar structure.
[0063] The full width at half maximum Hw of the D band D is 50 or more and 160 or less. The full width at half maximum Hw D can be 60 or more, 70 or more, 80 or more, or 90 or more, and can be 150 or less, 140 or less, or 130 or less. In particular, the full width at half maximum Hw D can be 90 or more and 130 or less.
[0064] The intensity I of the D band D relative to the intensity I of the G band G of the ratio I D / I G can be 1.0 or more and 1.6 or less. This ratio I D / I G can be 1.1 or more or 1.2 or more, and can be 1.5 or less or 1.4 or less. In particular, this ratio I D / I G can be 1.2 or more and 1.4 or less.
[0065] Furthermore, the D band is caused by the structure from the sp 3 orbital, and the G band is caused by the structure from the sp 2 orbital. Therefore I D / I G represents the ratio of the structure from the sp 3 orbital of the electrode active material to the structure from the sp 2 orbital. I D / I G being small means that the structure from the sp 2 orbital, i.e., the graphite structure, is more, and I D / I G being large means that the graphite structure is less.
[0066] The Raman spectrum of the electrode active material of the present disclosure can be obtained by Raman spectroscopy measurement (wavelength 532 nm). The baseline of the Raman spectrum can be set, for example, by performing baseline analysis with Spectra Manager of JASCO Corporation.
[0067] The electrode active material of the present disclosure can be obtained, for example, by firing a commercially available product of hard carbon in an inert atmosphere, and particularly can also be manufactured by the method for manufacturing an electrode active material described later.
[0068] "Method for Manufacturing Electrode Active Material"
[0069] The method for manufacturing an electrode active material of the present disclosure includes the following steps: providing a raw material containing carbon; and firing the raw material in an inert atmosphere containing more than 0% and less than 1.0% of air to carbonize it.
[0070] Conventionally, a method of carbonizing a raw material containing carbon by firing it in an inert atmosphere has been generally adopted. In this regard, the applicant of the present application unexpectedly found that by carbonizing a raw material containing carbon by firing it in an inert atmosphere containing a trace amount of air, the electrode active material of the present disclosure can be obtained. Although not limited to theory, it is considered that this is because the oxygen contained in the air preferentially oxidizes and removes parts other than nano-graphite, and thus the proportion of the nano-graphite part in the obtained carbon material becomes larger.
[0071] The method of the present disclosure includes providing a raw material containing carbon.
[0072] The raw material containing carbon is not particularly limited as long as it can be used to manufacture hard carbon. For example, the raw material containing carbon can be an organic compound such as an alcohol like ethanol, an aldehyde like phenols and formaldehyde, a phenolic resin, a resin such as polyacrylonitrile and polyimide, and a woody material such as a coconut shell. These raw materials can be used alone or in combination of multiple kinds.
[0073] The method of the present disclosure includes: carbonizing the raw material containing carbon by firing it in an inert atmosphere containing more than 0% and less than 1.0% of air. In the method of the present disclosure, the proportion of air contained in the inert atmosphere can be 0.1% or more, 0.2% or more, 0.3% or more, 0.4% or more, or 0.5% or more, and can be 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, or 0.5% or less.
[0074] The firing temperature is not particularly limited. The firing temperature can be, for example, 1000 °C or more, 1100 °C or more, 1200 °C or more, 1300 °C or more, 1400 °C or more, or 1500 °C or more, and can be 2000 °C or less, 1900 °C or less, 1800 °C or less, 1700 °C or less, 1600 °C or less, or 1500 °C or less.
[0075] The firing time can be 0.1 hour or more, 0.5 hour or more, 1 hour or more, or 2 hours or more, and can be 5 hours or less, 4 hours or less, 3 hours or less, or 2 hours or less.
[0076] Electrode mixture
[0077] The electrode mixture of the present disclosure contains the electrode active material of the present disclosure. The electrode mixture of the present disclosure may optionally contain a conductive additive and a binder. When the battery containing the electrode mixture of the present disclosure is a solid battery, the electrode mixture of the present disclosure may optionally contain a solid electrolyte.
[0078] In the present disclosure, "electrode mixture" refers to a composition that can form an electrode active material layer as it is or by further containing other components. In addition, in the present disclosure, "electrode mixture slurry" refers to a slurry that contains a dispersion medium in addition to the "electrode mixture" and can form an electrode active material layer by coating and drying.
[0079] <Electrode active material>
[0080] Regarding the electrode active material, reference can be made to the above description related to the electrode active material of the present disclosure. The electrode mixture of the present disclosure may contain 50% by mass or more or 70% by mass or more and 99% by mass or less or 95% by mass or less of the electrode active material.
[0081] <Conductive additive>
[0082] The conductive additive can be, for example, a carbon material, a metal material, etc. Specific examples of the carbon material can include carbon black such as acetylene black, Ketjen black, furnace black, thermal cracking carbon black; carbon fibers such as VGCF; graphite; hard carbon; coke, etc. As the metal material, Fe, Cu, Ni, Al, etc. can be cited. The content of the conductive additive in the electrode mixture is not particularly limited and can be appropriately determined according to the target conductivity.
[0083] <Binder>
[0084] As the binder, a chemically stable and electrostable binder can be used. Specific examples of the binder can include, for example, fluorine-based binders such as polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, etc.; rubber-based binders such as styrene-butadiene rubber (SBR)-based binders; olefin-based binders such as polypropylene (PP)-based binders, polyethylene (PE)-based binders, etc.; cellulose-based binders such as carboxymethyl cellulose (CMC)-based binders, or polyacrylic acid (PAA)-based binders. The content of the binder in the electrode mixture is not particularly limited and can be appropriately determined according to the target adhesiveness.
[0085] <Solid electrolyte>
[0086] The solid electrolyte may be an inorganic solid electrolyte. Examples of the inorganic solid electrolyte include an oxide solid electrolyte and a sulfide solid electrolyte. Examples of the oxide solid electrolyte include NASION-based compounds such as Na3Zr2Si2PO 12 and the like, and β-alumina (Na2O-11Al2O3). Examples of the sulfide solid electrolyte include Na2S-P2S5. The shape of the solid electrolyte may be, for example, particulate.
[0087] 《Battery》
[0088] As Figure 1 shown, the battery 100 of the present disclosure sequentially includes a negative electrode current collector layer 110, a negative electrode active material layer 120, an electrolyte layer 130, a positive electrode active material layer 140, and a positive electrode current collector layer 150, and either the negative electrode active material layer or the positive electrode active material layer contains the electrode binder of the present disclosure.
[0089] The battery of the present disclosure may be a primary battery or a secondary battery such as a lithium ion battery and a sodium ion battery. In particular, the battery of the present disclosure may be a sodium ion battery. The electrolyte layer of the sodium ion battery may contain sodium ions.
[0090] The battery of the present disclosure may be a liquid system battery or a solid battery. Furthermore, in the present disclosure, a "solid battery" refers to a battery that uses at least a solid electrolyte as an electrolyte. Therefore, a solid battery may also use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. In addition, the solid battery of the present disclosure may also be an all-solid battery, that is, a battery that uses only a solid electrolyte as an electrolyte. The electrolyte layer of the liquid system battery may contain an electrolytic solution having sodium ions. The electrolyte layer of the solid battery may contain a solid electrolyte having sodium ions.
[0091] Hereinafter, as an example, the materials constituting the battery of the present disclosure in the case where the battery of the present disclosure is a sodium ion battery will be described.
[0092] <Negative electrode current collector layer>
[0093] Examples of the material for the negative electrode current collector layer include SUS, aluminum, copper, nickel, carbon, and the like.
[0094] The negative electrode current collector layer may be, for example, in the form of a foil, a net, or a porous form.
[0095] <Negative electrode active material layer>
[0096] The negative electrode active material layer contains a negative electrode mixture, and the negative electrode mixture contains a negative electrode active material and optionally contains a solid electrolyte, a conductive additive, and a binder. In particular, the negative electrode mixture can be the electrode mixture of the present disclosure. That is, the negative electrode active material layer can contain the electrode mixture of the present disclosure. Regarding the electrode mixture of the present disclosure, reference can be made to the above description related to the electrode mixture of the present disclosure.
[0097] The negative electrode active material layer can have a certain thickness. The thickness of the negative electrode active material layer is not particularly limited and can be, for example, 0.1 μm or more and 1 mm or less.
[0098] <Electrolyte layer>
[0099] In the case where the battery of the present disclosure is a liquid system battery, the electrolyte layer can be formed by impregnating the separator with the electrolyte solution.
[0100] (Separator)
[0101] As the material of the separator, as long as it is a material having the function of electrically separating the negative electrode active material layer and the positive electrode active material layer, it is not particularly limited. For example, a porous sheet made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc., a non-woven fabric, a porous insulating material such as a glass fiber non-woven fabric, etc., or a combination thereof can be cited. The thickness of the separator is not particularly limited and can be, for example, 5 μm or more and 1 mm or less.
[0102] (Electrolyte solution)
[0103] The electrolyte solution can contain a sodium salt and a non-aqueous solvent. As the sodium salt, for example, inorganic sodium salts such as NaPF6, NaBF4, NaClO4, and NaAsF6; and organic sodium salts such as NaCF3SO3, NaN(CF3SO2)2, NaN(C2F5SO2)2, NaN(FSO2)2, and NaC(CF3SO2)3 can be cited.
[0104] As the non-aqueous solvent, as long as it is a solvent that dissolves the sodium salt, it is not particularly limited. For example, as a high dielectric constant solvent, cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), γ-butyrolactone, sulfolane, N-methyl-2-pyrrolidone (NMP), 1,3-dimethyl-2-imidazolidinone (DMI), etc. can be cited. On the other hand, as a low viscosity solvent, chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), acetate esters such as methyl acetate and ethyl acetate, ethers such as 2-methyltetrahydrofuran, etc. can be cited. A mixed solvent formed by mixing a high dielectric constant solvent and a low viscosity solvent can also be used.
[0105] In the case where the battery of the present disclosure is a solid battery, the electrolyte layer contains a solid electrolyte and may optionally contain a conductive additive and a binder.
[0106] Regarding the solid electrolyte, conductive additive, and binder, reference may be made to the above description related to the electrode mixture of the present disclosure.
[0107] <Positive electrode active material layer>
[0108] The positive electrode active material layer contains a positive electrode active material and may optionally contain a conductive additive and a binder. In the case where the battery of the present disclosure is a solid battery, the positive electrode active material layer may optionally contain a solid electrolyte.
[0109] When the negative electrode active material layer contains the electrode mixture of the present disclosure, examples of the positive electrode active material include Na-containing oxides such as layered active materials, spinel-type active materials, and olivine-type active materials. Specifically, examples include NaFeO2, NaNiO2, NaCoO2, NaMnO2, NaVO2, Na(Ni X Mn 1-X )O2(0 < X < 1), Na(Fe X Mn 1-X )O2(0 < X < 1), NaVPO4F, Na2FePO4F, Na3V2(PO4)3, etc. The shape of the positive electrode active material is not particularly limited. The positive electrode active material can be in the form of particles. In this case, its average particle diameter can be, for example, 1 nm or more or 10 nm or more, and can be 100 μm or less or 30 μm or less. The higher the content of the positive electrode active material in the positive electrode active material layer, the higher the capacity of the positive electrode. The positive electrode active material layer may contain, for example, 50% by mass or more or 70% by mass or more and 99% by mass or less or 95% by mass or less of the positive electrode active material.
[0110] Regarding the conductive additive, binder, and solid electrolyte, reference may be made to the above description related to the electrode mixture of the present disclosure.
[0111] The positive electrode active material layer may have a certain thickness. The thickness of the positive electrode active material layer is not particularly limited and can be, for example, 0.1 μm or more and 1 mm or less.
[0112] <Positive electrode current collector layer>
[0113] Examples of the material for the positive electrode current collector layer include SUS, aluminum, nickel, iron, titanium, carbon, etc.
[0114] The positive electrode current collector layer can be, for example, in the form of a foil, mesh, or porous material.
[0115] Furthermore, for example, when the battery of the present disclosure is a battery other than a sodium-ion battery, various materials commonly used in such a battery can be used.
[0116] <Other configurations>
[0117] The battery of the present disclosure may include a battery case that houses the respective layers of the battery, and terminals connected to a current collector or the like. In addition, in order to reduce the contact resistance, the battery of the present disclosure may include a restraining member that restrains the respective layers in the stacking direction. For these members, the same members as those in the prior art can be used.
[0118] Examples of the shape of the battery of the present disclosure include button type, laminated type, cylindrical type, and square type.
[0119] <<Method for manufacturing a battery>>
[0120] The method for manufacturing a battery of the present disclosure may include: forming an electrode active material layer containing the electrode binder of the present disclosure.
[0121] The method for forming the electrode active material layer may include: providing an electrode binder slurry containing the electrode binder of the present disclosure and a dispersion medium; and coating the electrode binder slurry on a substrate and then drying and removing the dispersion medium.
[0122] Regarding the electrode binder, reference can be made to the above description related to the electrode binder of the present disclosure.
[0123] The dispersion medium is not particularly limited, and examples thereof include alcohols, diols, cellosolves, amines, ketones, carboxamides, phosphoric acid amides, sulfoxides, carboxylic acid esters, phosphoric acid esters, ethers, nitriles, etc. Specifically, ethanol, 2-propanol, methyl ethyl ketone, and N-2-methylpyrrolidone can be exemplified.
[0124] The substrate is not particularly limited, but when the negative electrode active material layer contains the electrode binder of the present disclosure, it can be, for example, a negative electrode current collector layer.
[0125] The drying temperature, drying time, etc. can be appropriately designed according to the boiling point and usage amount of the dispersion medium.
[0126]
Examples
[0127] <<Production Example 1>>
[0128] <<Production of electrode active material>>
[0129] A commercially available spherical phenolic resin as a carbon-containing raw material was carbonized by firing at 1500 °C for 2 hours in an argon atmosphere mixed with 0.5% air to produce hard carbon. Thus, the electrode active material of Production Example 1 was obtained.
[0130] <<Production Example 2>>
[0131] Using commercially available coconut shell pieces as the carbon-containing raw material, the electrode active material of Production Example 2 was obtained in the same manner as in Production Example 1 except for this.
[0132] 《Production Example 3》
[0133] KURANODE (manufactured by Kuraray Co., Ltd.), which is a carbon material, was fired at 2000 °C in an argon atmosphere. Thus, the electrode active material of Production Example 3 was obtained.
[0134] 《Comparative Production Example 1》
[0135] CARBOTRON P S(F) type (manufactured by Kureha Corporation), which is a carbon material, was fired at 1200 °C in an argon atmosphere. Thus, the electrode active material of Comparative Production Example 1 was obtained.
[0136] 《Comparative Production Example 2》
[0137] The firing temperature was set to 1500 °C, and the electrode active material of Comparative Production Example 2 was obtained in the same manner as in Comparative Production Example 1 except for this.
[0138] 《Example 1》
[0139] <Preparation of Electrode Binder>
[0140] The electrode active material of Production Example 1 as the negative electrode active material and polyvinylidene fluoride (PVdF) as the binder were dispersed in N-methyl-2-pyrrolidone (NMP) so that the mass ratio was 95:5, and stirred and mixed at 2000 rpm for 10 minutes. Thus, a slurry-like electrode binder (electrode binder slurry) as the negative electrode binder was obtained.
[0141] <Formation of Electrode Active Material Layer>
[0142] Using a 75-μm bar coater, the obtained electrode binder slurry was coated on an aluminum (Al) current collector foil as the negative electrode current collector layer and dried at 80 °C for 30 minutes. After punching the laminate of the negative electrode current collector layer and the dried electrode binder into φ16 mm, compression molding was performed using a press machine so that the electrode density became 1.0 g / cc. Thus, an electrode active material layer as the negative electrode active material layer was formed on the negative electrode current collector layer.
[0143] <Fabrication of Evaluation Cell>
[0144] Using a laminate of the negative electrode current collector layer and the electrode active material layer as the negative electrode, metallic sodium (Na) as the counter electrode, a 50-μm glass separator as the separator, and 1 M NaPF6 with EC:DMC = 1:1 (volume ratio) as the electrolyte, a 2032-type coin cell was fabricated.
[0145] "Evaluation"
[0146] "Determination Based on Raman Spectroscopy"
[0147] By Raman spectroscopy measurement (wavelength 532 nm), the Raman spectra of each case were obtained. The baseline of the Raman spectrum was set by performing baseline analysis with Spectra Manager of JASCO Corporation.
[0148] "Charge-Discharge Test"
[0149] In an environment of 25 °C, a charge-discharge test was performed at a voltage range of 0.01 to 1.5 V and a current value of 0.1 C to evaluate the Na insertion capacity (charge capacity) and Na extraction capacity (discharge capacity) of the button cell. Calculate the low-potential capacity, that is, the capacity of 0.05 to 0.01 V (vs. Na / Na + ) among the obtained Na insertion capacities, as the capacity below 0.05 V (vs. Na / Na + ).
[0150] "Examples 2 to 4 and Comparative Examples 1 to 5"
[0151] In the preparation process of the electrode mixture, the types of electrode active materials were changed as shown in Table 1. Except for this, evaluation units of Examples 2 to 4 and Comparative Examples 1 to 5 were obtained in the same manner as in Example 1 and evaluated.
[0152] "Results"
[0153] The Raman spectra of Example 1 and Comparative Example 3 obtained by Raman spectroscopy are shown in Figure 2 and Figure 3 ( Figure 2 : Example 1, Figure 3 : Comparative Example 3). In addition, the ratio I G’ of the intensity I of the G' band based on the Raman spectrum to the intensity I of the G band G , the full width at half maximum Hw of the D band G’ and the ratio I G of the intensity I of the D band to the intensity I of the G band D are shown in Table 1. In addition, the results of the charge-discharge test are shown in Table 1 and D of the intensity I of the G band G to the ratio I D / I G . Figure 4 .
[0154] Table 1
[0155]
[0156] As shown in Figure 2As shown, in the electrode active material of the present disclosure of the embodiment, in the Raman spectrum, it is confirmed that there is a G' band in the vicinity of 2800 to 2600 cm -1 On the contrary, in the electrode active material of the comparative example, the G' band was not confirmed in the Raman spectrum.
[0157] As shown in Table 1 and Figure 4 shown, I G’ / I G and the full width at half maximum Hw of the D band D For the cells of the embodiments within the scope of the present disclosure, the capacity at low potential is large. In particular, for the cells of Embodiments 1 and 2 where the full width at half maximum Hw D is 90 or more and 130 or less, the capacity at low potential is even greater.
Claims
1. An electrode active material comprising hard carbon, The hard carbon has a G' band, a G band and a D band in the Raman spectrum. The intensity of the G' band (I G’ ) relative to the intensity of the G band (I G ) ratio (I G’ / I G ) is 0.05 or more, and The half-peak width (Hw D ) is greater than 50 and less than 160.
2. The electrode active material according to claim 1, wherein the half-peak width (Hw D ) is greater than 90 and less than 130.
3. The electrode active material according to claim 1, wherein the intensity of the D band (I D ) relative to the intensity of the G band (I G ) ratio (I D / I G ) is greater than or equal to 1.0 and less than or equal to 1.
6.
4. The electrode active material according to claim 3, wherein the intensity of the D band (I D ) relative to the intensity of the G band (I G ) ratio (I D / I G ) is greater than or equal to 1.2 and less than or equal to 1.
4. 5 . An electrode mixture comprising the electrode active material according to claim 1 .
6. A battery comprising, in order, a negative electrode current collector layer, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer and a positive electrode current collector layer, and Any one of the negative electrode active material layer and the positive electrode active material layer contains the electrode mixture according to claim 5 . 7 . The battery according to claim 6 , wherein the negative electrode active material layer contains the electrode mixture according to claim 5 . 8 . The battery according to claim 6 , which is a sodium ion battery in which the electrolyte layer contains sodium ions. 9 . The battery according to claim 8 , which is a liquid-type battery in which the electrolyte layer contains an electrolytic solution containing sodium ions. 10 . The battery according to claim 8 , which is a solid battery in which the electrolyte layer includes a solid electrolyte containing sodium ions.
11. A method for producing an electrode active material according to any one of claims 1 to 4, comprising the following steps: providing a feedstock comprising carbon; and The raw material is fired in an inert atmosphere containing more than 0% and less than 1.0% of air to be carbonized.
Citation Information
Patent Citations
Conductive material, porous material, and manufacturing method thereof, and electrode material and power storage devices
JP2021012872A
Sodium secondary cell
WO2012147242A1